Comparative analysis of omega-3 fatty acid desaturase FAD7A-1 chloroplastic gene in castor: COMPARATIVE ANALYSIS OF OMEGA-3 FATTY ACID DESATURASE FAD7A-1 CHLOROPLASTIC GENE - KARUNASHREE; G C SHEKHAR; B KISAN; B V TEMBHURNE; CHANNABASAVA; ANIL JADHAV; S BHARATHI (Journal of Oilseeds Research, 2023)
Omega-3 Polyunsaturated fatty acids (PUFAs) are characterized by the presence of a double bond, three atoms away from the terminal methyl group in their chemical structure. These fatty acids play a crucial role in promoting health benefits. Castor, known for its applications in traditional medicine and as a lubricant, has been historically employed for its pain-relieving properties and enhancement of muscle activity. In the present study the omega-3 fatty acid desaturase FAD7A-1 chloroplastic (P48619, FAD3C_RICCO) gene sequence of castor was obtained from the NCBI data base was analyzed for its diversity, amino acid composition and phylogenetic relatedness with other species harboring the gene. The phylogenetic tree of 13 aligned sequences clustered into two clusters and the amino acids varied between the species evaluated.